EFEKTIVITAS ABDOMINAL MASSAGE TERHADAP KONSTIPASI PADA PASIEN PERAWATAN HIGH CARE UNIT (HCU) BEDAH SARAF - Bahtiar Yusuf (Jurusan Keperawatan Poltekkes Kemenkes Sorong, 2023)
Constipation is a common problem that occurs in gastrointestinal function. The prevalence of constipation in the general population is around 20% (Roque & Bouras, 2015). Constipation is also interpreted as a symptom, not a disease (WGO, 2019). Constipation is often found in intensive care patients in hospitals (Dehghan, Fatehi, & Mehdipoor, 2018). In Indonesia constipation affects almost 20% in children and adolescents (Oswari et al., 2018). The causes are immobility, hypotension, use of vasopressors and opioid medications medications (Gacouin et al., 2010; Hanson & Siddique, 2018). Abdominal Massage (AM) is a gentle massage on the abdomen that has been used as a massage therapy for clients with constipation (Graneheim & Jacobsson, 2011). AM performed in a supine position, with head and knee support, and sitting and standing positions (Mcclurg et al., 2017). To determine the effectiveness of abdominal massage in patients with constipation. Materials and methods : In this quasi experiment there were 20 respondents in the HCU neurosurgery room divided into 10 intervention groups and 10 control groups. The intervention group performed AM for 15 minutes which was carried out twice a day for three days, while the control group only received standard care. The degree of constipation, intestinal peristalsis, client satisfaction, family ability in AM, and effective cos are measured. Results : The degree of constipation decreased significantly in the intervention group and increased significantly in the control group (P = 0,008). After the intervention, the prevalence of constipation decreased significantly in the intervention group. There were significant differences between the two groups regarding intestinal peristalsis, normal in the intervention group and abnormal in the control group (P <0,002). Client satisfaction increased significantly in the intervention group (P = 0,005). Family ability increases in the intervention group and strengthens family relationships with clients. Cos is effective and therapy is feasible long-term for clients with constipation.